Disturbance of consciousness and involuntary movements caused by pregabalin. (28th November 2012) - Shimizu, Taro; Yoshida, Tsuneyasu; Kitamura, Koichi; Hamada, Osamu
Abstract : A 91-year-old man with chronic low-back pain presented with 1-day history of disturbance of consciousness and myoclonus of all of his extremities and face. Laboratory examinations revealed no abnormalities. Administration of benzodiazepine for the myoclonus resulted in immediate and complete disappearance of the symptoms. He recently started taking pregabalin (Lyrica capsules) which was prescribed for low-back pain 3 days ago. The day following admission, he discontinued pregabalin. He did not experience recurrence of his symptoms any more. We concluded that the neurological symptoms he experienced were possibly due to pregabalin.